Practical enterprise React : become an effective react developer in your team - Duldulao, Devlin Basilan; Cabagnot, Ruby Jane Leyva (Apress, 2021)
Learn to write a real-world enterprise app using the fundamentals of React and the most popular React libraries. Knowing the basics of React is important, but what is more important is knowing the common third-party libraries and how to use them. The book is perfect for intermediate to experienced React developers or busy React developers who would like to get things done and have maintainable React code. Practical Enterprise React features popular libraries such as React Router v6 for route navigation, Redux with Saga and Thunk for state management, and Formik with Yup for form and input validations. You'll also work with Material UI 5 (the next major version of the most popular UI component library in React), Axios as the HTTP client library, JWT auth for client app authentication, and TypeScript. Finally, you'll learn to deploy the app to Netlify, and containerize the React app to ship it as a standalone container instance or in a Kubernetes cluster. Become a more effective React developer by using what is available out there instead of trying to reinvent the wheel. This book reveals how to save time and money, and build better apps for your clients. Get practical with React enterprise app development and enhance your career. You will: Use TypeScript in React and React Hooks Work with Redux Toolkit, and TypeScript Build an inventory dashboard, charts, and calendar Write forms with Formik Validate inputs with Yup Use Material UI for fast user interface building Secure your React app by building a login form and protecting the routes.